Material Hardship among Lower-Income Households: The Role of Liquid Assets and Place. Issue 5 (29th July 2022) - Despard, Mathieu R.; Taing, Valerie; Weaver, Addie; Roll, Stephen; Grinstein-Weiss, Michal
ABSTRACT: Lower income households are at risk for material hardship, particularly amidst the economic fallout of COVID-19. Where one lives (e.g., suburb, small town) may affect this risk due to variable access to resources, yet the evidence is mixed concerning the influence of place. We used a pooled, national cross-sectional sample of 66, 046 lower-income tax filers to examine differences in material hardship in rural, small town, micropolitan, and urban areas. Controlling only for standard demographic variables, hardship risk appears higher in non-urban areas, yet these differences disappear after controlling for financial characteristics such as liquid assets and home ownership.